DETERMINING FACTORS OF FIRM SURVIVABILITY A STUDY OF UNIVERSITY SPIN-OFFS IN INDONESIA - Muhammad Afif Sallatu; Nurul Indarti (Journal of Indonesian Economy and Business (JIEB), 2018)
Nowadays, universities in many countries are encouraged to take their research products to the next level by translating them into commercialized products to benefit society at large. In doing so, they establish a firm, a so-called University Spin-Off (USO), which specializes in carrying out the mission. A USO is a firm which is established to optimize or commercialize the Intellectual Property Rights (IPRs) of the university. Previous studies into USOs, documented in the extant literature, have mainly focused on investigating the initial process of the USOs’ establishment, such as the drivers to initiate the USOs. Only a little attention has been paid to investigate the various drivers affecting the development of the USOs. Studies into the survivability of USOs are relatively limited. The current study is intended to fill this gap. Additionally, the findings are expected to add to the existing literature on USOs, particularly in the context of developing countries. This study aims at identifying the factors affecting the USOs’ survival. We used the resource-based view and contingency theory to identify and understand the various factors (internal and external) that might affect a USO’s survivability. Data for this study were collected through a survey. From the literature, we identified ten relevant factors for a USO’s survivability and 41 items to operationalize them, which we then used to develop a questionnaire. The factors are the USO’s business orientation, human resources’ reputation, product innovation, business plan, business models’ innovation, social networks, export activities, capital access, government support, and the business’s incubator. The data were collected from 111 USOs established by 14 universities located in five big cities in Indonesia. The survey was conducted from February until May 2017. Before performing the regression analysis, we deployed a factor analysis to validate the instruments and found that all the 41 items were valid and fell into ten component factors. The analysis found that there were only two factors which significantly affected the USO’s survivability: Its human resources’ reputation and social networks. These findings lead us to a conclusion that building a good reputation and maintaining its social networks are very important to ensure the survivability of a USO.